الذات المنكسرة وتجلياتها في الشعر الملحون المغاربي – قصيدة الشمعة لابن الرزين أنموذجا – (El-Wahat Journal for Research and Studies, 2025)
Throughourstudy, weseek to identify the manifestations of the presence of the broken self in the Maghreb popularpoetictext, and itsability to presentitsinteriority and emotionalexperiences, by focusing on the experience of the Maghreb popularpoet Ibn al-Razin, taking the poem “The Candle,” known in the Maghreb poeticheritage, as a model for application, as itrepresents a reflectingmirror of refraction. himself and hisinternalconflict, not to mention his feeling of distraction and loss in the face of a reality that inspires despair and depression, dictated by a number of subjective and objective factorsthatcontributed to nourishing the contents of the poem.Keywords: saltypoetry, Ibn al-Razin, candle, self, brokenness